A cartography of the Ethics Committees of the Polytechnic Higher Education in Portugal (2023) (Práxis Educativa, 2023)
This is a descriptive study, of qualitative methodology, carried out in 2023, with the general objective of characterising the Ethics Committees of Polytechnic Higher Education in Portugal, as well as identifying the factors that hinder and facilitate the action of this Committees. A contextualization is carried out through a literature review and a description of the legislative framework. Document analysis was carried out and data were collected in interviews with the presidents of the Committees (a total of 16). It was found that the Ethics Committees began to be created in 2009 and that they currently exist in 75% of the institutions. The characterization findings are presented and discussed (number of members, external members, gender, age, qualifications, training in ethics/bioethics and experience in committee). Difficulties and facilitating factors were organized into thematic groups, whose synthesis is presented. It is considered that this is a necessary path of development at a global level, in Higher Education Institutions.Keywords: Ethics Committees. Higher Education. Polytechnic Education.